2016
DOI: 10.1556/032.2016.66.4.6
|View full text |Cite
|
Sign up to set email alerts
|

Technical efficiency and total factor productivity in the Kazakh banking industry

Abstract: This paper investigates the technical efficiency and productivity of Kazakh commercial banks over the period 2000–2013. Non-parametric approaches, namely the Data Envelopment Analysis and the Malmquist index are employed to calculate technical efficiency and productivity. In addition, a second-stage regression is also estimated to identify the determinants of efficiency. The results indicate that banks in Kazakhstan operate below their optimum levels, with larger banks being more efficient than smaller ones. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…They found that Egyptian banking sector experienced a decline in TFP growth at the rate of 2.55% in the whole sample period 1997-03. (Kasman and Mekenbayeva, 2016) Examined TE and TFP for Kazakh commercial banks from 2000 to 2013. Results indicated that banks in Kazakhstan operated below their optimum levels.…”
Section: Literature Reviewmentioning
confidence: 99%
“…They found that Egyptian banking sector experienced a decline in TFP growth at the rate of 2.55% in the whole sample period 1997-03. (Kasman and Mekenbayeva, 2016) Examined TE and TFP for Kazakh commercial banks from 2000 to 2013. Results indicated that banks in Kazakhstan operated below their optimum levels.…”
Section: Literature Reviewmentioning
confidence: 99%
“…-foreign direct investments and oil prices (Aizhan, Makaevna, 2011;Arazmuradov, 2016;Kalyuzhnova, Patterson, 2016;Khoich, 2012;Kupalova, Tulebayeva, 2012); -total factors productivity (Kasman, Mekenbayeva, 2016;Ziyadin, 2012); -financial integration process in the Eurasian Economic Union (Falkowski, 2012;Kebekpaeva, 2012;Knobel, 2015;Tarr, 2016); -financial sector reforms (Akimov, Dollery, 2008;Ruziev, Majidov, 2013); -stock market performing and banking sector stability (Grishko, Murzakhmetov, 2015;Nichkasova, Shmarlouskaya, Sadvokassova, 2019).…”
Section: Theory: Importance Of the Financial Market To The Local Economymentioning
confidence: 99%
“…The financial system remains fragile and vulnerable to external shocks. The banking system is undergoing a period of adaptation to new prudential requirements, which negatively affect its ability to credit the economy (Kasman and Mekenbayeva, 2016;Ruziev and Majidov, 2013;Ziyadin, 2012). According to researchers, despite a high level of penetration of the banking system into the economy (more than 90% of enterprises have bank accounts), only 19% of them had access to lending (OECD, 2016).…”
Section: Introductionmentioning
confidence: 99%